ANALISIS ETIKA KEPEMIMPINAN KEPALA DINAS TERHADAP PENYELENGGARAAN PELAYANAN PUBLIK DI KOTA PALU (Studi Kasus Pada Dinas Pekerjaan Umum, Energi Dan Sumber Daya Mineral) - Arman Arman (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
This study aims to (1), to review and analyze the ethical leadership of public works, energy and mineral resources of the public service in the city of hammers. (2), to examine and analyze what factors are a barrier to leadership of the department of public works, energy and mineral resources of the public service in the city of hammers. The results showed that the ethical leadership of public works, energy and mineral resources of the public service in the city of hammers, can be said to be good, although the expected results have not been up this look on treating her subordinate level and the ability of the head of department of public works, energy and mineral resources in carrying out its duties and functions as a leader look less good, while inhibiting factor to leadership of departments of public works, energy and mineral resources of the public service in the city of hammering, lack of coordination and less willing to hear any complaints / suggestions / aspirations of the people.